Strategi Inovatif Dalam Mengintegrasikan Kurikulum Merdeka pada pendidikan Agama Islam - Ahmad Aziz Mubaroq; Neng Andri Tya Fasha; Reda Fujiana Pasrah; Fikra Muhammad Nazib (Advances In Education Journal, 2025)
Innovation in Islamic Religious Education Learning within the Independent Curriculum. This research discusses innovative strategies in integrating the Independent Curriculum into Islamic Religious Education (PAI) learning through a systematic literature review approach. (SLR). The Merdeka Curriculum aims to encourage contextual and real-life relevant learning. The three main innovations highlighted are: first, Blended Learning, which combines face-to-face and online learning to enhance flexibility. Second, Flipped Classroom, where students study the material at home and class time is used for interactive discussions. Third, Project-Based Learning, which involves relevant projects to develop critical, creative, and collaborative skills. Studies show that these strategies enhance students' understanding and interest in Islamic values. However, challenges such as limited resources and teacher readiness still exist. Effective solutions include intensive training, access to technology, and contextual strategies. With the right steps, PAI in the Merdeka Curriculum can shape students' dynamic and relevant character in the modern era.